Respon Dan Adaptasi Masyarakat Terhadap Pembangunan Jalan Jalur Lingkar Selatan (JJLS) Kecamatan Temon Daerah Istimewa Yogyakarta - , FERY JOKO SUSILO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to identify the community's response and adaptation to the presence of the southern ring road lanes (jalan jalur lingkar selatan, JJLS) and to identify the factors that determine the diversity of the community response and adaptation. In addition it will study the pattern of growth as a result of the southern ring road construction. The research was conducted in the District Temon, Kulon Progo Regency of Yogyakarta Special Region. The method of research is using field survey